2016
DOI: 10.1371/journal.pone.0148465
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Modeling of the Late-Gestation Fetal Pituitary Response to Transient Hypoxia

Abstract: BackgroundThe late-gestation fetal sheep responds to hypoxia with physiological, neuroendocrine, and cellular responses that aid in fetal survival. The response of the fetus to hypoxia represents a coordinated effort to maximize oxygen transfer from the mother and minimize wasteful oxygen consumption by the fetus. While there have been many studies aimed at investigating the coordinated physiological and endocrine responses to hypoxia, and while immunohistochemical or in situ hybridization studies have reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Previous efforts have largely focused on the effects of acute hypoxemic injury to fetal and neonatal animal models. Limited studies have shown the effects of acute hypoxemia on fetal and neonatal brain transcriptomic profiles including upregulation of chemokines, 17 purine binding and signaling, 18 and hypoxia-inducible transcription factor–dependent genes and apoptosis-promoting factors. 16 However, these studies were not designed to accurately model the effects of chronic hypoxemia in a fetus with CHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous efforts have largely focused on the effects of acute hypoxemic injury to fetal and neonatal animal models. Limited studies have shown the effects of acute hypoxemia on fetal and neonatal brain transcriptomic profiles including upregulation of chemokines, 17 purine binding and signaling, 18 and hypoxia-inducible transcription factor–dependent genes and apoptosis-promoting factors. 16 However, these studies were not designed to accurately model the effects of chronic hypoxemia in a fetus with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we compared the brain transcriptome of fetal sheep in the EXTEND system supported under normoxemic versus chronically hypoxemic conditions, which are similar to those found in a human fetus with CHD. While there have been previous fetal brain transcriptome studies looking at the effects of acute hypoxemia on fetal brains in multiple animal models, 16 , 17 , 18 to our knowledge this is the first transcriptomics study investigating the effects of chronic hypoxemia at levels similar to those seen in severe CHD on the fetal brain ( Video 1 ).…”
mentioning
confidence: 99%
“…All of these responses have been described previously as the primary early cellular response to other fetal hypoxia models in the pituitary gland (Wood et al . ) and hypothalamus (Wood et al . ) at 1 h post stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Among transcription factors regulating the significantly altered sets several could be related to hypoxia/ischemia, a known consequence of MDMA administration (Ferrington et al, 2006). For example, the Pax4 regulated gene set was downregulated after transient hypoxic condition in the fetal pituitary of sheep (Wood et al, 2016). FoxO1 and FoxO4 were implicated in antioxidant mechanisms after brain ischemia (Abbas et al, 2009; Fukunaga and Shioda, 2009; Araujo et al, 2011; Jenwitheesuk et al, 2017).…”
Section: Discussionmentioning
confidence: 99%